A novel bone registration method using impression molding and structured‐light 3D scanning technology. Issue 10 (4th February 2022) - He, Guangyu; Ricca, Jacob M.; Dai, Amos Z.; Mustahsan, Vamiq M.; Cai, Yanming; Bielski, Michael R.; Kao, Imin; Khan, Fazel A.
Abstract: Accurate bone registration is critical for computer navigation and robotic surgery. Existing registration systems are expensive, cumbersome, limited in accuracy and/or require intraoperative radiation. We recently reported a novel method of registration utilizing an inexpensive, compact, and X‐ray‐free structured‐light 3D scanner. However, this technique is not always practical in a real surgical setting where soft tissue and blood can obstruct the continuous line‐of‐sight required for structured‐light technology. We sought to remedy these limitations using a novel technique using rapid‐setting impression molding to capture bone surface features and scan the undersurface of the mold with a structured‐light scanner. The photonegative of this mold is compared to the preoperative computed tomography (CT)‐scan to register the bone. A registration accuracy study was conducted on 36 CT‐scanned femur sawbones, simulating typical exposure in hip/knee arthroplasty and bone tumor surgery. A cadaver experiment was also conducted to evaluate the feasibility of using the impression molding in a more realistic operating room setting. The registration accuracy of the proposed technique was 0.50 ± 0.19 mm. This was close to the reported accuracy of 0.43 ± 0.18 mm using a structured‐light scanner without impression molding ( p  = 0.085). In comparison, historical values for "paired‐point" and intraoperative CT image‐based registration methods currently used in modern robotic/computer‐navigation systems were 0.68 ± 0.14 mm ( p  = 0.004) and 0.86 ± 0.38 mm, respectively. The registration accuracy of the cadaver experiment was consistent with that of sawbone experiments. Although future studies are needed to extend to human subjects, this study shows that the impression molding method can produce comparable or better registration accuracy than the existing techniques.